Trends in the incidence of the Epstein-Barr virus-associated malignancies extranodal NK/T-cell lymphoma and nasopharyngeal carcinoma in Taiwan. - Shyh-An Yeh; Liang-Chun Chiu; Hsin-Chieh Lin; Hung-Ju Li; Sheng-Fung Lin; Yu-Chieh Su (PLoS ONE)
Nasopharyngeal carcinoma (NPC) and extranodal NK/T-cell lymphoma (ENKTL) are associated with the Epstein-Barr virus (EBV). The current study aimed to evaluate the trends in the incidence of ENKTL and NPC in Taiwan within the last 15-30 years. To assess the incidence of ENKTL from 2008 to 2021 and NPC from 1995 to 2021, an epidemiological study was performed using population-based registry data from the Taiwan Cancer Registry. The secular trends in the annual incidence rates were expressed as average annual percent change (AAPC). During the study period, 872 new ENKTL diagnoses and 39412 new NPC diagnoses were reported. The annual age-adjusted incidence rates of ENKTL and NPC decreased significantly, with an AAPC of -2.47 (p = 0.014) and -1.16 (p < 0.001), respectively. The incidence rates of NPC from 1995 to 2021 in the 20-44-, 45-64-, and ≥65-year-old age groups decreased from 5.23 to 4.42 per 100,000 person-years (AAPC = -0.45, p = 0.011), from 15.28 to 11.36 per 100,000 person-years (AAPC = -1.21, p < 0.001), and from 10.48 to 7.24 per 100,000 person-years (AAPC = -1.91, p < 0.001), respectively. The age-specific incidence rates of ENKTL in the 45-64-year-old age group significantly decreased from 0.46 to 0.32 per 100,000 person-years during 2008-2021 (AAPC = -3.37, p = 0.008). The incidence of ENKTL between 2008 and 2021 in the 20-44- and ≥65-year-old age groups also decreased from 0.16 to 0.11 per 100,000 person-years and from 0.87 to 0.79 per 100,000 person-years, respectively. Interestingly, the EBV seroprevalence in Taiwan remained stable from 1984 to 2007. Nonetheless, there was a downward trend in the EBV seroprevalence in early childhood, with a decrease of approximately 20% in children aged 4 years and nearly 50% in children aged <2 years. Based on these findings, the downward trend in the incidence of NPC/ENKTL could be affected by the decline in early EBV infection rates. Considering that the EBV seroprevalence remained stable but the incidence rate of early EBV infection decreased during the same period, delayed EBV infection or factors other than EBV might play an important role in the downward trend in the incidence of NPC/ENKTL in Taiwan. Nevertheless, further investigations should be performed to assess these results.